2013
DOI: 10.5194/acpd-13-6455-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

European atmosphere in 2050, a regional air quality and climate perspective under CMIP5 scenarios

Abstract: To quantify changes in air pollution in Europe at the 2050 horizon, we designed a comprehensive modelling system that captures the external factors considered to be most relevant and relies on up-to-date and consistent sets of air pollution and climate policy scenarios. Global and regional climate as well as global chemistry simulations are based on the recent Representative Concentrations Pathways (RCP) produced for the Fifth Assessment Report (AR5) of IPCC whereas regional air quality modelling is based on t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 69 publications
5
30
1
Order By: Relevance
“…There is a slight increase (1%) between 2005 and 2050 in the reference scenario which is explained by a joint effect of global warming and long-range transport of pollution from outside Europe (Colette et al, 2013a) which counterbalances the effects of the European atmospheric policy (Fig. 1b).…”
Section: Exposure To Air Pollution and Associated Health Impactsmentioning
confidence: 92%
See 2 more Smart Citations
“…There is a slight increase (1%) between 2005 and 2050 in the reference scenario which is explained by a joint effect of global warming and long-range transport of pollution from outside Europe (Colette et al, 2013a) which counterbalances the effects of the European atmospheric policy (Fig. 1b).…”
Section: Exposure To Air Pollution and Associated Health Impactsmentioning
confidence: 92%
“…Thus these scenarios represent the most up-to date basis for analysing air pollution related issues, particularly at a regional scale. These scenarios were used before in Rao et al (2012) or Colette et al (2012Colette et al ( , 2013a, although these studies were limited to air quality and/or health impacts and did not include any cost-benefit analysis.…”
Section: Climate -Air Quality Modelling Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible effects of climate change on air quality are complex: for example, it is generally predicted that a warmer climate could lead to a slight increase in pollution levels, while an increase in precipitation can lead to pollution decrease (e.g. Colette et al, 2013;Fiore et al, 2012;Isaksen et al, 2009;Jacob and Winner, 2009). Model studies have shown that the climate impact on future air quality is in general much smaller than the impact of change in emissions.…”
Section: Discussionmentioning
confidence: 96%
“…Tagaris et al (2007) estimated that the summertime DM8H ozone levels over the United States could decrease by 20% (regionally varying from À11% to À28%) by the combined effects of climate change and emission reductions. The projection of air quality and climate at the regional scale over Europe in 2050 was performed under 5th Coupled Model Intercomparison Project (CMIP5), and the main factor that drives future air quality projections was found to be air pollutant emissions rather than climate change or intercontinental transport of pollution (Colette et al, 2013).…”
Section: Introductionmentioning
confidence: 99%